Large eddy simulation of focused breaking waves with different wave steepness. (November 2022) - Cui, Ting; He, Guanghua; Jiang, Meirong; Wang, Weizhi; Yuan, Lihao; Han, Duanfeng; Kamath, Arun; Bihs, Hans
Abstract: The profile of fluid field and wave geometry, kinematic and dynamic characteristics of focused breaking waves in finite water depth with different wave steepness are studied with a constant wave steepness wave focusing method in this paper. The flow field is solved by the two-phase flow model in REEF3D based on the incompressible Navier–Stokes equation and the Large Eddy Simulation (LES) model to simulate the complex breaking process. The numerical model is validated by comparing wave elevation of both focused non-breaking and breaking case with the experimental results and satisfactory agreements are achieved. A series of simulation cases with different global steepness are carried out to analyze the focused waves of different breaking types. The difference between the preset focused condition and the real ones and the area of air cavity rolled by the wave jets are both indicates that the process of wave focusing and breaking show a strong nonlinear profile. The maximum values of the horizontal velocity occur after the impingement moment and can reach 2.5 C p for extreme steep waves. Three typical wave breaking criteria in finite water depth are calculated and discussed successively. For the geometric criterion analysis, the global wave steepness and local steepness have a good performance both for predicting wave breaking and presenting the breaking intensity. The kinematic breaking criterion ratio shows that the previous threshold 1 at the breaking incipient scenario is not sufficient to predict the wave breaking. Besides, it is found that the time interval when the kinematic breaking criterion ratio big than 1 may related to the wave breaking type. The energy changing rate for both the focusing and dissipation processes increase linearly with the global wave steepness and show a good ability as a dynamic breaking criterion and also prove the asymmetric profile of breaking waves. Highlights: Focused Spilling and plunging breaking waves are both simulated in deep water. Three typical breaking criteria were discussed when predicting wave breaking onset. Geometry, kinematics, and energy are discussed for different breaking intensity. Time interval of exceeding particle velocity strongly relates to the breaking type. A new dynamic breaking criterion based on energy dissipation rate are proposed.